Vejrforholdene i Landbrugsaaret 1943—44. (Fra 1. Oktober 1943 til 30. September 1944). - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1943—44. (Fra 1. Oktober 1943 til 30. September 1944).